Public Toilet - Gautam, Anugya; Bhattarai, Kritika; Shrestha, Annada; Khanal, Pratikshya; Shrestha, Kailash (KEC Journal of Science and Engineering, 2024)
The provision of public toilets is not only a matter of land use but also an essential design and planning concern. It is an essential infrastructure to guarantee the right to sanitation in public spaces. Given this, the present research aims to understand the perspective of public toilet on the basis of planning, innovative approaches, universal access and sustainable features. For this research, two cases of public toilets were studied. On the whole, the importance of the public toilet on the basis of different innovative approaches, planning and universal access is highlighted in this study with regard to health, sanitation, and accessibility issues.